2001
DOI: 10.2527/2001.7951132x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characteristics and relative bioavailability of supplemental organic copper sources for poultry.

Abstract: Five commercially available organic Cu products and reagent-grade CuSO4 x 5H2O (Cu Sulf) were evaluated by polarographic analysis and solubility in 0.1 M K2HPO4-KH2PO4 buffer (pH 5), 0.2 M HCl-KCl buffer (pH 2), or deionized water. Fractions from these solubility tests were evaluated by gel filtration chromatography for structural integrity. The organic sources were Cu lysine complex (Cu Lys), Cu amino acid chelate (Cu AA), Cu proteinate A (Cu ProA), Cu proteinate B (Cu ProB), and Cu proteinate C (Cu ProC). Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 0 publications
0
64
1
2
Order By: Relevance
“…Further Cu-supplementations from inorganic and/or organic sources did not significantly improve turkeys performance and health. Other authors (Guo et al, 2001;Banks et al, 2004a) reported also that copper source did not affect broiler performance. MIKULSKI D. ET AL.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Further Cu-supplementations from inorganic and/or organic sources did not significantly improve turkeys performance and health. Other authors (Guo et al, 2001;Banks et al, 2004a) reported also that copper source did not affect broiler performance. MIKULSKI D. ET AL.…”
Section: Discussionmentioning
confidence: 90%
“…When Cu sulphate was assigned a value of 100% as the standard, linear regression slope ratios of log 10 liver Cu concentration regressed on added dietary Cu concentration gave estimated relative bioavailability values of 124, 122 and 111% for Cu lysine complex, Cu amino acid chelate and Cu proteinate, respectively. The bioavailability estimates for Cu lysine complex and Cu amino acid chelate were greater (P≤0.05) than that for Cu sulphate (Guo et al, 2001). Aoyagi and Baker (1993) reported that the relative bioavailability of Cu in a Lysine-Cu complex was 126% compared with 100% for that in copper sulphate.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Secondly, gastrointestinal pH may be increased as the result of the buffering capacity of NSP, with the indirect result of reduction in gastrin secretion in response to the more alkaline environment (Dilger et al, 2004). Metalamino acid chelated mineral has been shown to evidence better absorption, which has been reported by many researchers to enhance the effi ciency of its use (Yu et al, 2000;Guo et al, 2001). However, our data evidenced no improvements in the MAC treatments, the different supplemented level and mineral type from that utilized in other experiments may be a reasonable explanation for the differences observed in the current study.…”
Section: Resultsmentioning
confidence: 99%